Magic and magicians in the Middle Ages and the early modern time : the occult in pre-modern sciences, medicine, literature, religion, and astrology - Classen, Albrecht (Fundamentals of medieval and early modern culture, 2017)
There are no clear demarcation lines between magic, astrology, necromancy, medicine, and even sciences in the pre-modern world. Under the umbrella term 'magic, ' the contributors to this volume examine a wide range of texts, both literary and religious, both medical and philosophical, in which the topic is discussed from many different perspectives. The fundamental concerns address issue such as how people perceived magic, whether they accepted it and utilized it for their own purposes, and what impact magic might have had on the mental structures of that time. While some papers examine the specific appearance of magicians in literary texts, others analyze the practical application of magic in medical contexts. In addition, this volume includes studies that deal with the rise of the witch craze in the late fifteenth century and then also investigate whether the Weberian notion of disenchantment pertaining to the modern world can be maintained. Magic is, oddly but significantly, still around us and exerts its influence. Focusing on magic in the medieval world thus helps us to shed light on human culture at large.